Development of the “selective concentration” analytical method for drug-containing hair regions based on micro-segmental analysis to identify a trace amount of drug in hair: hair analysis following single-dose ingestion of midazolam - Kuwayama, Kenji; Miyaguchi, Hajime; Kanamori, Tatsuyuki; Tsujikawa, Kenji; Yamamuro, Tadashi; Segawa, Hiroki; Okada, Yuki; Iwata, Yuko T. (Forensic toxicology, 2021)
Purpose Hair can be the only available specimen to prove drug-facilitated crimes (DFCs). However, it is difficult to identify drugs abused in DFCs, particularly benzodiazepines ingested in a single dose, using the conventional segmental hair analysis. In this study, an analytical procedure to identify a trace amount of drug in hair based on micro-segmental analysis was developed. Methods Hair was donated from a subject who had been administered midazolam in a single dose. First, tens of hair strands were analyzed according to our routine procedure. Drug screening and identification were performed using a quadrupole-Orbitrap liquid chromatography–tandem mass spectrometry (LC–MS/MS) instrument. Next, two hair strands were segmented at 0.4-mm intervals and multi-target selected reaction monitoring of each segment (micro-segmental analysis) was performed using a tandem quadrupole LC–MS/MS instrument. After distribution curves of midazolam-derived ions in each hair strand were constructed, the residual extracts from segments corresponding to drug-containing regions were collected selectively into one tube. The extract was concentrated using solid-phase extraction and then injected into the LC–MS/MS instrument for drug identification. Results We failed to identify drugs using our routine procedure, although a slight peak, predicted to arise from midazolam, was detected, while the peak detected in the concentrated extract from drug-containing hair regions (named “selective concentration”) was identified as midazolam. Conclusions The “selective concentration” enabled the identification of a trace amount of drug using several hair strands. The method would be helpful in proving DFCs even after it was impossible to identify drugs using conventional segmental hair analysis.